Sources of Productivity Spillovers: Panel Data Evidence from China - Badi H. Baltagi; Peter Egger; Michaela Kesina (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper assesses sources of productivity spillovers in China's electric and electronic manufacturing industry using a rich panel data-set of 25,360 firms observed over the period 2004-2007. This industry is characterized by its important reliance on technology. In particular, the paper focuses on the role of other firms' productivity as well as productivity shifters in affecting own firm-level total factor productivity. In addition, this paper examines the possible difference between spillovers from foreign-owned units and from units which participate at global markets through exporting in comparison to domestically-owned and non-exporting units. We find evidence of stronger spillovers from exporting firms than from non-exporting firms. This is true for foreign-owned as well as domestic exporters. The strength of the spillover effects differ across subsectors.
Keywords: C23; C31; D24; L65; 330; technology spillovers; spatial econometrics; panel data econometrics; firm-level productivity; Chinese firms